2018 Asian Games Success: Policies for the Development of Indonesian Elite Athletes - Rahadian, Adi; Ma’mun, Amung; Berliana, Berliana; Nuryadi, Nuryadi (Universitas Suryakancana, 2021)
The success of elite sports in Indonesia plays an important role in building and constructing national identity. Along its development, the success of sport is pictured as symbol of national resurrection and sport winner as national icon. Status and power of sports Indonesia among other countries is measured by the country’s success of having achievement in international sport events. Elit sport development are implemented through sport introduction stage, monitoring, fostering, also developing talent and improving achievement (UU SKN No. 3 Tahun 2005). The system of elite sport development in Indonesia which is oriented to: a) build elite’s facility; b) support for athletes; c) provide training and sport science; and d) centered competition opportunity (Pelatnas) in the preparation of international competition. This study explores the sports achievements of Indonesia with the aims of maximizing the policy of elite sport development in Indonesia. The achievements of elite sports are the pride of the country, including obtaining diplomatic recognition, ideological competition and a belief that the success of sports in international level gives benefit for socio-politic in the nation, starting from feeling pleased, optimistic and giving impact economically, especially in relation to organizing elite sports competitions.Keyword: achievement, elite athlete, Indonesia, national identity, sport development